Phenotypic and molecular phylogeny of Klebsiella pneumoniae isolated from respiratory-diseased pet cats in Iraq. - Al Galebi, Ahlam A S; Al Hassani, Mithal K A; Kadhim, Hadaf Mahdi; Gharban, Hasanain A J (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Investigation of Klebsiella pneumoniae in respiratory-diseased pet cats, estimation of antibiotic sensitivity, and molecular phylogeny of local K. pneumoniae to identify its identity to global isolates. Methods: Totally, 127 feline cases with various respiratory signs were selected for the collection of the nasal swabs that were cultured to isolate K. pneumoniae and detect the antibiotic sensitivity. Further molecular phylogeny of positive K. pneumoniae isolates was done. Results: Findings of culture media and biochemical tests showed that 26.77% of nasal swabs were positive samples for K. pneumoniae. The screening for the antibiotic susceptibility reported a higher sensitivity to ceftiofur, ciprofloxacin, cefepime, amikacin, gentamicin, cefotaxime, and meropenem, as well as ceftazidime, ceftriaxone, and doxycycline, imipenem, as well as clotrimazole and tetracycline. In contrast, the more significant resistant K. pneumoniae isolates were detected to clarithromycin, clindamycin, amoxicillin, cefixime, chloramphenicol, erythromycin, cephalexin, cefadroxil, azithromycin, and nalidixic acid, whereas, significant semi-sensitivity was shown to tylosin. Molecular testing by polymerase chain reaction demonstrated that all isolates were K. pneumoniae. The genetics-based analysis of local K. pneumoniae isolates recorded an overall similarity (95.47%–100%) and changes/mutations (0.0004%–0.0084%), in particular to the National Center for Biotechnology Information-Iraqi isolate (Lc732203.1). Conclusion: This study indicates the high prevalence of K. pneumoniae in respiratory-diseased cats with significant appearance of antibiotic resistance in study isolates. Sequencing data referred to the close related association of study isolates to human K. pneumoniae isolates, suggesting the increased prevalence of nosocomial infections in veterinary medicine. J. Adv. Vet. Anim. Res., 12(2): 621–628, June 2025 http://doi.org/10.5455/javar.2025.l926